Cultivating Scientific Literacy: Developing A Biodiversity E-Module Based on Socioscientific Issues and Local Potential - Perdana Putra, Erik; April Yanti, Fitri; Walid, Ahmad (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The existing literacy program in the higher education has not successfully translated into effective science learning, resulting in students lacking awareness of the significance of scientific literacy in their daily lives. This study aims to analyse the validity, practicality and effectiveness of using biodiversity e-module based on socioscientific issues and local potential to improve students’ scientific literacy. The method employed in this research is the research and development (R&D) method using the ADDIE model. The participants of this study are 37 fourth-semester students enrolled in the Tadris IPA Program at UIN Fatmawati Sukarno Bengkulu, who are taking the biodiversity course in the academic year 2023/2024, consisting of one class. Data collection was conducted through an indirect communication approach using instruments such as validation questionnaires and tests to obtain data on scientific literacy achievements. The findings of this study are the utilization of biodiversity teaching materials grounded in socio-scientific issues and local potential is highly suitable for implementation in science education. The instructional materials exhibit a commendable feasibility level, meeting the criteria for good feasibility. This indicates that the teaching materials are readily comprehensible for students. Moreover, the developed teaching materials prove effective in enhancing four key facets of scientific literacy such as the body of knowledge, science as a way of investigation, science as a way of thinking and the interaction of science and technology and society.